Molecular mechanisms underlying the effect of pioglitazone therapy in Non-Alcoholic Steatohepatitis (NASH) - Abdul Rahim, Roslina; Aithal, Guruprasad Padur; Macdonald, Ian A.; Bennett, Andrew J. (Elsevier, Inc., 2009)
Background and Aim: A recent randomised double-blind placebocontrolled trial (RCT) demonstrated that Pioglitazone therapy was effective in reducing hepatocellular injury and fibrosis in subjects with NASH. We aimed to investigate the molecular mechanisms underlying the effects of Pioglitazone in NASH. Methods: Liver biopsy samples collected from 46 non-diabetic subjects before and after 1-year treatment with 30 mg/day of Pioglitazone or placebo were used for RNA and protein extraction. 200 ng of total RNA was used to synthesise cDNA for gene expression using Taqman RealTime Polymerase Chain Reaction (RT-PCR). Results: See Table 1. Table 1: Effects of 12 months of Pioglitazone treatment on gene expression. Target gene Pre-trial (n = 22) Pioglitazone (n = 12) Placebo (n = 12) P Value ChREBP 2.156 ±0.435b 3.971 ±1.049b 2.117 ±0.520 0.049b SREBP-1C 1.478 ±0.258a 2.150 ±0.610c 0.310 ±0.062a,c 0.022a, 0.002c CPT-1 0.492 ±0.156 0.793 ±0.275 0.476 ±0.136 NS PDK4 1.679 ±0.369 2.137 ±0.481 0.842 ±0.295 NS PK2 1.549 ±0.363 1.317 ±0.377 1.227 ±0.337 NS GCK 0.658 ±0.284 0.794 ±0.374 1.401 ±0.725 NS Gene expression values are normalised using the geometric mean of the reference genes (beta actin and hydroxymethylbilane synthase). Data are presented as mean ± SEM. Carbohydrate regulatory element binding protein (ChREBP), Sterol regulatory element binding protein-1C (SREBP-1C), Carnitine palmitoyl transferase-1 (CPT-1), Pyruvate dehydrogenase kinase 4 (PDK4), Pyruvate kinase 2 (PK2) and Glucokinase (GCK). aPre-trial vs Placebo; bPre-trial vs Pioglitazone; cPioglitazone vs placebo) Conclusions: Pioglitazone therapy caused a significant upregulation of both ChREBP and SREBP-1C gene which are both involved in the transcriptional regulation of lipogenesis. Conversely, patients given placebo showed marked reduction in the SREBP-1C by the end of the trial period. It is unclear at present as to the mechanism by which Pioglitazone therapy increases lipogenic transcription factor levels. These findings may reflect the improved whole body insulin sensitivity observed in the Pioglitazone treated group. Alternatively the increase in ChREBP and SREBP-1C may be caused by direct effects of Pioglitazone activation of PPAR- g (Peroxisome proliferator-activated receptor- g) in the liver.